Telaah Teori Inflasi Menurut Al-Maqrizi dalam Perspektif Ekonomi Islam - Darul, Muhammad Ghalib (JSE: Jurnal Sharia Economica, 2025)
Inflation is an economic phenomenon that affects not only price stability but also reflects the moral condition and governance of a country. In the perspective of Islamic economics, Al-Maqrizi, a 15th-century Muslim thinker, viewed inflation as a consequence of moral degradation, weak governance, and uncontrolled money circulation. This study aims to examine Al-Maqrizi’s thoughts on inflation in depth, including its definition, classification, causes, and proposed solutions. Using a qualitative descriptive method through literature review, this research highlights Al-Maqrizi’s classification of inflation into natural inflation—caused by environmental factors—and man-made inflation—resulting from corruption, excessive taxation, and over-issuance of paper money. Al-Maqrizi proposed Sharia-based solutions, such as moral reform, the use of gold and silver currencies (dinar and dirham), and fair wealth distribution. His ideas are highly relevant in addressing contemporary economic challenges. By integrating spiritual, moral, and technical dimensions, Al-Maqrizi’s perspective offers a valuable contribution to developing just and sustainable Islamic economic policies.